Makna Pantun pada Upacara Adat Perkawinan Masyarakat Melayu di Desa Sorek 2 Kecamatan Pangkalan Kuras Kabupaten Pelalawan - Chindi Amelia Suciana; Rahayu, Sri (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
Pantun is an orderly and structured bound language that can provide direction, guidance, direction, and guidance. The language used in rhymes can also be studied in terms of meaning, one of which is denotative and connotative meaning. The problem studied in this study is what is the meaning of the rhyme at the traditional marriage ceremony of the Malay community in Sorek 2 Village, Pangkalan Kuras District, Pelalawan Regency? This study aims to describe, analyze, and interpret the denotative and connotative meanings of the rhyme at the traditional Malay marriage ceremony in Sorek 2 Village, Pangkalan Kuras District, Pelalawan Regency. The theory used in this study is the theory of Chaer (2009) and (2012). The method used in this research is descriptive method. Data collection techniques used in this study are documentation techniques and interview techniques. Based on the results of the study, it can be concluded that 1) From 200 lines of rhymes in 50 rhymes that the author describes, there are 179 data on denotative meanings in marriage rhymes in Sorek 2 Village, Pangkalan Kuras District, Pelalawan Regency, and 2) From 200 lines of rhymes in 50 stanzas In the rhyme that the author describes, there are 21 connotative meaning data in marriage rhymes in Sorek 2 Village, Pangkalan Kuras District, Pelalawan Regency.